A Systematic Literature Review on the Digitalization of Ethnomathematics in 101 Tower Taiwan - Agus Suyono; Lisnani Lisnani (Universitas Negeri Surabaya, 2025)
This study presents a systematic literature review exploring the integration of ethnomathematics in the context of the iconic Taipei 101 Tower through digitalization. The research aims to identify how mathematical concepts embedded in the cultural, architectural, and symbolic elements of the 101 Tower can be utilized in educational settings, particularly within the framework of digital learning tools. A total of 25 peer-reviewed articles published between 2013 and 2024 were selected using PRISMA methodology, focusing on keywords such as